2016
DOI: 10.4172/2329-9517.s1-008
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Magnesium Deficiency in the Cardiovascular System and their Relationships to Cardiovascular Diseases and Atherogenesis

Abstract: The authors present evidence for a novel, new hypothesis whereby magnesium deficiency (MgD) acts as a genotoxic agent which probably causes numerous, hertofore, unrecognized consequences, even over a short-term, on the physiological, molecular and biochemical machinery of cardiovascular tissues and cells. The end result of these genotoxic effects of MgD probably plays important roles in the etiology and generation of diverse cardiovascular diseases, atherosclerosis, inflammation, and strokes via alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Our results, also encourages the idea that, water intake (e.g., from tap waters, well waters, bottled waters, beverages using tap/well/spring waters, or desalinated waters) should contain at least 25-40 mg/liter/day of Mg 2+ [58][59][60]76,77,81]. In this context, our group has performed several conclusive experiments and highlighted most of the detrimental pathophysiological implications of Mg deficiency, which includes decreased cardiac output, decreased myocardial contractility, decreased coronary blood flows, mitochondrial release of cytochrome C, lipid peroxidation of cardiac and vascular muscle membranes, increased cellular levels of NO and p53, release of cytokines and chemokines, increased cellular entry of calcium ions and overload, increases in membrane permeability, myocardial acidification, loss of cellular ATP, DNA damage, shortening of telomeres, apoptosis, and necroptosis [11,41,42,57-61,72-79-83].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Our results, also encourages the idea that, water intake (e.g., from tap waters, well waters, bottled waters, beverages using tap/well/spring waters, or desalinated waters) should contain at least 25-40 mg/liter/day of Mg 2+ [58][59][60]76,77,81]. In this context, our group has performed several conclusive experiments and highlighted most of the detrimental pathophysiological implications of Mg deficiency, which includes decreased cardiac output, decreased myocardial contractility, decreased coronary blood flows, mitochondrial release of cytochrome C, lipid peroxidation of cardiac and vascular muscle membranes, increased cellular levels of NO and p53, release of cytokines and chemokines, increased cellular entry of calcium ions and overload, increases in membrane permeability, myocardial acidification, loss of cellular ATP, DNA damage, shortening of telomeres, apoptosis, and necroptosis [11,41,42,57-61,72-79-83].…”
mentioning
confidence: 75%
“…Employing transmission electron microscopy (TEM), in our Mg-deficient rabbit experimentation suggested to us that, both the vascular smooth muscle cells and macrophages of the lipid-laden arterial vessels exhibited necrosis and apoptosis [16,65,66, unpublished findings of Stempak, BT Altura, M Brust and BM Altura]. Further, investigation using TEM on cardiac and arterial muscle cells of Mg-deficient rats also showed clear signs of necrosis as well as apoptosis [66][67][68][69][70][71][72][73][74][75][76][77][78]; N Shah, BT Altura and BM Altura, unpublished findings]. Experimentation with high-power TEM revealed that, these Mg-deficient muscle cells exhibited what is now termed "necroptosis".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have provided putative evidence that magnesium (Mg) deficient environments can behave like genotoxins on cardiovascular tissues and cells. [3][4][5] We continue this line of thought, below, for believing Mgdeficient environments can result in inflammatory lesions which can result in atherogenesis, thus leading to heart attacks, ischemic heart disease (IHD), cardiac failure (CF), sudden-death ischemic heart disease (SDIHD), and strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and human studies have demonstrated an inverse relationship between dietary intake of Mg and atherosclerosis. [3][4][5]17,19,[22][23][24][25][26][27][28][29][30][31] The myocardial level of Mg has consistently been observed to be lower in subjects dying from IHD and SDIHD in soft-water areas than those in hard-water areas. 17,[19][20][21][22][23][24][25]32 Mg plays critical roles in more that 500 enzymatic reactions in the body, 33 and is required for all energygenerating reactions and oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%